2019
DOI: 10.1051/epjap/2019190013
|View full text |Cite
|
Sign up to set email alerts
|

The growth of silver nanostructures on porous silicon for enhanced photoluminescence: The role of AgNO3 concentration and deposition time

Abstract: Silver nanostructures were obtained by using the electrodeposition method on n-type porous silicon (PSi) under different deposition times and concentrations of AgNO3 solutions. The analyses of the structural and photoluminescence properties of PSi/Ag were studied by SEM, XRD and photoluminescence spectroscopy. SEM analysis showed that the shape and size of Ag nanostructures significantly depend on the deposition time and concentration. It was found that spherical nanoparticles and thin Ag dendrites were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…An increase of the photoluminescence intensity could also be observed by electrodepositing Ag particles from an AgNO 3 solution by varying the deposition time and the concentration of the electrolyte [59]. This behavior of the luminescence is furthermore shown after LiCl treatment of porous silicon as well as an enhancement of the minority carrier lifetime due to the passivation of the dangling bonds at the silicon surface [60].…”
Section: Optical Properties Of Microporous Siliconmentioning
confidence: 76%
“…An increase of the photoluminescence intensity could also be observed by electrodepositing Ag particles from an AgNO 3 solution by varying the deposition time and the concentration of the electrolyte [59]. This behavior of the luminescence is furthermore shown after LiCl treatment of porous silicon as well as an enhancement of the minority carrier lifetime due to the passivation of the dangling bonds at the silicon surface [60].…”
Section: Optical Properties Of Microporous Siliconmentioning
confidence: 76%
“…Both films (a) and (b) exhibit a broad peak at 2 θ = 26° with a shoulder one at 24.5° which corresponds to the semi-crystalline structure of BOPET substrate. 38,40,41 The height peak of the (111) diffraction of Ag was used to calculate the average crystalline size using the Scherrer formula, D=k.λ/βcosθ, where k is the phase factor 0.94, λ is the wavelength of X-rays =1.54056 Å, β is the full width at half maximum(FWHM), and θ is the angle of diffraction. The calculated average crystalline sizes are equal to 9 and 7 nm for the elaborated films (a) and (b), respectively.
Figure 4.XRD spectra (Panel a) and Raman spectrum (Panel b) of PPy-Ag films deposited on: (a) untreated BOPET substrate and (b) deposited on APTMS-treated BOPET, respectively.
…”
Section: Resultsmentioning
confidence: 99%
“…It has also found that smaller spherical silver nanoparticles coalesce and form silver nanorods that grow upwards from the surface (Figure 3 (a)). The growth process of Ag structures could be described by diffusion-limited aggregation (DLA) model [23]. Initially, Ag + ions take electrons to create silver particles on the PI which was treated with KOH.…”
Section: Methodsmentioning
confidence: 99%
“…In the spectrum of the PI/Ag/ ZnO, the absorption peak appeared about 300 nm, is the characteristic peak correspond to the exciton absorption of ZnO. It should be noted that for the sample of PI/Ag, there is not observed any absorption peak at about 400 nm, corresponding to the surface plasmon resonance (SPR) in silver nanostructures, because of the formation of discontinuous but interconnected Ag nanorods layer [23,27].…”
Section: Optical Measurementsmentioning
confidence: 97%